Modelling the 3D microstructure and performance of solid oxide fuel cell electrodes: Computational parameters - Cai,Q; Adjiman,CS; Brandon,NP (Electrochimica Acta, 2011)
In this paper, the computational parameters for a 3D model for solid oxide fuel cell (SOFC) electrodes developed to link the microstructure of the electrode to its performance are investigated. The 3D microstructure model, which is based on Monte Carlo packing of spherical particles of different types, can be used to handle different particle sizes and generate a heterogeneous network of the composite materials. Once formed, the synthetic electrodes are discretized into voxels (small cubes) of equal sizes from which a range of microstructural properties can be calculated, including phase volume fraction, percolation and three-phase boundary (TPB) length. Transport phenomena and electrochemical reactions taking place within the electrode are modelled so that the performance of the synthetic electrode can be predicted. The degree of microstructure discretization required to obtain reliable microstructural analysis is found to be related to the particle sizes used for generating the structure; the particle diameter should be at least 20–40 times greater than the edge length of a voxel. The structure should also contain at least 253 discrete volumes which are called volume-of-fluid (VOF) units for the purpose of transport and electrochemical modelling. To adequately represent the electrode microstructure, the characterized volume of the electrode should be equivalent to a cube having a minimum length of 7.5 times the particle diameter. Using the modelling approach, the impacts of microstructural parameters on the electrochemical performance of the electrodes are illustrated on synthetic electrodes.